Daniel Azpiazu y Martín Schorr (2010), Hecho en Argentina. Industria y Economía, 1976-2007, Buenos Aires, Siglo XXI Editores, 2010 - MARIO RACCANELLO (H-Industri@, 2010)
Daniel Azpiazu y Martín Schorr (2010), Hecho en Argentina. Industria y Economía, 1976-2007, Buenos Aires, Siglo XXI Editores, 2010